2011
DOI: 10.1177/1741826711422988
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of an internet-based computer-tailored expert system for physical activity in patients with heart disease

Abstract: Patients with CHD using an Internet-based activity prescription with online coaching were more physically active at follow up than those receiving usual care. Use of the CardioFit program could extend the reach of rehabilitation and secondary-prevention services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
246
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(252 citation statements)
references
References 21 publications
3
246
2
1
Order By: Relevance
“…98,97,[100][101][102][103]106,107,109 Overall, the technology that was used most often to increase physical activity was the Internet through Web sites, online tutorials, or networking opportunities. Many of the programs that used the Internet also used other forms of technology, including pedometers and feedback messages via e-mail.…”
Section: Review Of Evidence For the Efficacy Of Mobile Technologybasementioning
confidence: 99%
See 1 more Smart Citation
“…98,97,[100][101][102][103]106,107,109 Overall, the technology that was used most often to increase physical activity was the Internet through Web sites, online tutorials, or networking opportunities. Many of the programs that used the Internet also used other forms of technology, including pedometers and feedback messages via e-mail.…”
Section: Review Of Evidence For the Efficacy Of Mobile Technologybasementioning
confidence: 99%
“…Of the 9 studies that used the Internet as the main intervention component, 5 reported significant differences between groups in increasing physical activity. 98,100,102,106,107 The outcomes differed in each study and included increases in step counts, increases in moderately vigorous physical activity, increases in moderate physical activity, and increases in minutes per week of physical activity. Two of the 14 studies examined the use of SMS, 103,109 and both reported significant differences between the intervention and control or comparative conditions.…”
Section: Review Of Evidence For the Efficacy Of Mobile Technologybasementioning
confidence: 99%
“…Studies were conducted in Canada,22 31 34 Australia,33 Belgium,25 Brazil,32 France,27 Korea,29 the Netherlands,28 New Zealand30 and the USA,26 and published between 2002 and 2014. Sample sizes varied from 1534 to 242 22.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, these programs began as group sessions based in outpatient centers or hospitals, but subsequent variations have emerged over the last 2 decades, including individual home-based models of care using information manuals, case-managers, phone and Internet support. [7][8][9][10][11] The evolution of and variation in what is meant by cardiac rehabilitation therefore highlights the need for clear and precise reporting of the exact intervention used.…”
mentioning
confidence: 99%